Discovery of benzochalcone derivative as a potential antigastric cancer agent targeting signal transducer and activator of transcription 3 (STAT3). (31st December 2022) - Dong, Jinyun; Yang, Jing; Yu, Wenkai; Li, Haobin; Cai, Maohua; Xu, Jing-Li; Xu, Han-Dong; Shi, Yun-Fu; Guan, Xiaoqing; Cheng, Xiang‑Dong; Qin, Jiang‑Jiang
Abstract: Gastric cancer remains a significant health burden worldwide. In continuation of our previous study and development of effective small molecules against gastric cancer, a series of benzochalcone analogues involving heterocyclic molecules were synthesised and biologically evaluated in vitro and in vivo . Among them, the quinolin-6-yl substituted derivative KL-6 inhibited the growth of gastric cancer cells (HGC27, MKN28, AZ521, AGS, and MKN1) with a submicromolar to micromolar range of IC50, being the most potent one in this series. Additionally, KL-6 significantly inhibited the colony formation, migration and invasion, and effectively induced apoptosis of MKN1 cells in a concentration-dependent manner. The mechanistic study revealed that KL-6 could concentration-dependently suppress STAT3 phosphorylation, which may partly contribute to its anticancer activity. Furthermore, in vivo antitumour study on the MKN1 orthotopic tumour model showed that KL-6 effectively inhibited tumour growth (TGI of 78%) and metastasis without obvious toxicity. Collectively, compound KL-6 may support the further development of candidates for gastric cancer treatment.